Cooperative Clinical Trial of Photodynamic Therapy for Early Gastric Cancer With Photofrin Injection® and YAG-OPO Laser. Issue 4 (1998) - Mimura, Seishiro; Narahara, Hiroyuki; Hirashima, Toshio; Fukutomi, Hisayuki; Nakahara, Akira; Kashimura, Hiromasa; Matsui, Hirofumi; Tanimura, Hiroshi; Nagai, Yugo; Suzuki, Shigeru; Murata, Yoko; Yoshida, Kazunari; et al.
Abstract : Background and Objective : Photodynamic therapy (PDT) treats malignant tumors using photosensitizers and light. We employed a new pulse laser as the excitation light source for PDT, i.e. an optical parametric oscillator (OPO) system pumped by a Q -switched Nd:YAG laser, because it provides extremely high peak power. Study Design/Materials and Methods : The effects of PDT using the photosensitizer Photofrin ® and the new laser were evaluated in 12 patients with early gastric cancer. Results : Complete responses (CR) were obtained in 75% of 12 assessable patients, CR was observed in all cases with mucosal carcinoma (response rate 100%). Regarding toxicity, mild photosensitivity was seen in one case and it lasted several weeks. The other major side effect was decrease of total protein, which was observed in six patients (40%), lasting several months. There were no serious abnormalities in symptoms or laboratory tests. Conclusion : We conclude that the YAG-OPO laser is suitable as an excitation light source for PDT.